Evaluating the Rutting Resistance of Asphalt Concrete Modified With Organo-philic Montimorillonite Nano Clay (Ommt) - John Asonya (Uganda Christian University, 2025)
The long term performance of asphalt pavements is a major consideration in designing durable and safe road infrastructure, especially in low and middle income countries where flexible pavements dominate due to their lower cost and ease of maintenance. Rutting, a critical form of permanent deformation occurring in wheel paths, remains one of the most detrimental pavement failures, contributing to traffic accidents and accelerated deterioration. This study evaluated the effectiveness of organophilic montmorillonite (OMMT) Nano clay in improving the rutting resistance of asphalt concrete by enhancing its mechanical and volumetric properties. Unlike studies that use untreated montmorillonite, this research employed OMMT to achieve better binder filler interaction and dispersion within the asphalt matrix. Marshall mix design results identified 1.0% OMMT by mass of aggregate as the optimum dosage, producing a Marshall Stability of 17.2kN, Flow of 3.6mm, Air Voids of 4.2%, VMA of 15.3%, VFB of 72.4%, and a bulk density of 3.352g/cm³. Indirect tensile strength test confirmed that OMMT significantly reduces rutting susceptibility by strengthening the binder phase and improving stress distribution within the aggregate structure under heavy axle loading.
Undergraduate Research